2017
DOI: 10.1080/07391102.2017.1409651
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as potent allosteric inhibitors of protein tyrosine phosphatase 1B: molecular dynamics simulation and free energy calculation

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a member of the PTP superfamily which is considered to be a negative regulator of insulin receptor (IR) signaling pathway. PTP1B is a promising drug target for the treatment of type 2 diabetes, obesity, and cancer. The existence of allosteric site in PTP1B has turned the researcher's attention to an alternate strategy for inhibition of this enzyme. Herein, the molecular interactions between the allosteric site of PTP1B with three non-competitive flavonoids, (MOR), (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…During previous years, many QSAR studies have been done to aid the analysis and design of novel PTB1B inhibitors [ 41 ]. In silico studies have shown flavonoids to possess PTP1B-inhibitory activity [ 42 ]. In this study, the QSAR models of the flavonoids with PTP1B were generated to analyze the correlations of the structural molecular descriptors with inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…During previous years, many QSAR studies have been done to aid the analysis and design of novel PTB1B inhibitors [ 41 ]. In silico studies have shown flavonoids to possess PTP1B-inhibitory activity [ 42 ]. In this study, the QSAR models of the flavonoids with PTP1B were generated to analyze the correlations of the structural molecular descriptors with inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Zargari et al 73 investigated the molecular interactions between α7 helix and a previously proven the most potent flavonoids namely, MOR (Figure 9) (K i = 5.9 μM), MOK (Figure 9) (K i = 3.15 μM), and DPO (Figure 9) (K i = 2.5 μM). [74][75][76] In terms of the molecular docking analysis, the binding energy was found to be correlated with experimental K i values for each allosteric flavonoid inhibitor; DPO bound to PTP1B with the least binding energy (−8.3 kcal/mol) followed by MOK (−6.5 kcal/mol) and MOR (−5.3 kcal/mol).…”
Section: Natural Plant Products As Ptp1b Allosteric Inhibitorsmentioning
confidence: 99%
“…Furthermore, a cutoff of 12 Å for long-range and LINKS algorithms for H-bond constraints were applied ( Hess et al, 1997 ). The equilibration and production run H-bond outlines between the ligand and AChE were calculated using the g H-bond module of Gromacs, as detailed previously ( Zargari et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%